2007
DOI: 10.1039/b710143k
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and structural properties of hydrogels formed by chitosan, in the presence and absence of poly(vinylpyrrolidone) and sodium decylsulfate

Abstract: The structure of chemically-crosslinked chitosan and chitosan-poly(vinylpyrrolidone) (PVP) hydrogels is investigated by means of the combined use of small-angle neutron scattering (SANS), electron paramagnetic resonance spectroscopy (EPR), intradiffusion, and swelling degree measurements. These hydrogels may be described in terms of an inhomogeneous structure composed by polymer-rich and polymer-poor regions. The polymer-rich regions, whose correlation distance zeta is ranged between approximately 600 and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The values for 1.5 wt % chitosan gel are ξ = 549 ± 44 Å (pH = 5) and ξ = 616 ± 84 Å (pH = 4). These values are in reasonable agreement with those obtained by G. Mangiapia and co-workers who have investigated the structure of chemically cross-linked chitosan by means of the combined use of small-angle neutron scattering (SANS), electron paramagnetic resonance spectroscopy (EPR), intradiffusion, and swelling degree measurements. These authors have demonstrated that these hydrogels may be described in terms of an inhomogeneous structure composed by polymer-rich and polymer-poor regions.…”
Section: Resultssupporting
confidence: 91%
“…The values for 1.5 wt % chitosan gel are ξ = 549 ± 44 Å (pH = 5) and ξ = 616 ± 84 Å (pH = 4). These values are in reasonable agreement with those obtained by G. Mangiapia and co-workers who have investigated the structure of chemically cross-linked chitosan by means of the combined use of small-angle neutron scattering (SANS), electron paramagnetic resonance spectroscopy (EPR), intradiffusion, and swelling degree measurements. These authors have demonstrated that these hydrogels may be described in terms of an inhomogeneous structure composed by polymer-rich and polymer-poor regions.…”
Section: Resultssupporting
confidence: 91%
“…The correlation lengths, x, are within the range for chitosan hydrogels determined in other studies. 36,52 As a guide, the length of a chitosan monomer is $5.5 A ˚,53 which implies that a length of 115-135 A ˚is equivalent to segment of chitosan chain composed of $21 to 25 monomers. The x increases with increasing chitosan concentration, which may be because the larger number of polymer chains decreases mobility and rotation of each bond within a chain.…”
Section: Small Angle Neutron Scatteringmentioning
confidence: 99%
“…The structure of a chitosan-poly(vinylpyrrolidine) (PVP) hydrogel with potential for a drug delivery system has been reported. 36 The structure is described in terms of a polymer-rich region (characteristic length $600 to 850 A ˚) comprising a network with correlation length $90 A ˚(see eqn (3) and (4) for definition of characteristic and correlation length). The structure of a chitosan-GP hydrogel has recently been investigated on the micron length scale by laser scanning confocal microscopy (LSCM).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the water-insolubility and extend its applications, a number of water-soluble chitosan derivatives have been studied. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] The investigations indicated that some chitosan derivatives, such as (2-hydroxyl-3-dodecanoxyl) propyl-carboxymethylchitosan (HDP-CMCHS), (2-hydroxypropyl-3-butoxy) propyl-succinylchitosan (HBP-SCCHS), and (2-hydroxyl-3-butoxyl) propyl carboxymethyl-chitosan (HBP-CMCHS) are soluble, have good interfacial activity and form aggregates in concentrated solutions, contributing to their utilization in drug delivery. [12][13][14][15] In addition, HBP-CMCHS and carboxymethylchitosan (CMCHS) have been used in controlling the crystallization of CaCO 3 via the strong electrostatic interaction between the CMCHS -COO − groups and Ca 2+ ions, permitting the dispersion in aqueous solutions of the resulting CaCO 3 particles.…”
Section: Introductionmentioning
confidence: 99%